Mites (Acari, Gamasida) occuring in fruiting bodies of Aphyllophorales - Gwiazdowicz, Dariusz J. (1966– ); Łakomy, Piotr (1966– ); Polska Akademia Nauk. Muzeum i Instytut Zoologii (Museum and Institute of Zoology, PAS, 2002)
The Gamasida mites were studied in basidiocarpsof 11 species of fungi belonging to the Aphyllophorales. One hundred and twenty-six fruiting bodies were colected and 2528 mites from 76 species were found inside them. The genus Hoploseiushas not been recorded previously in Europe but it is recorded here. Most of the mite species were also found in other habitats, particularly litter. There was a high frequency of Aceoseius muricatus, Lasioseius ometesand Trichouropoda obscurasimilis in basidiocarps which might suggest the existance of preference for sporocarps as a habitat. The greatest number of mite species (33) were observed in Fomes fomentarius fruiting bodies. Also, a preliminary dependence analysis between mite and fungi species was done.
Bibliogr. p. 88
P. 81-89 ; 25 cm
Abstarct in Polish. Taxa in Latin.
Keywords: Mesostigmata; basidiocarps; Aphyllophorales; fungus; Fungi; Poland; arachnids; Arachnida; mites and ticks; acarines; Acarina; Acari; mesostigmatid mites; gamasids